2004
DOI: 10.1002/ptr.1511
|View full text |Cite
|
Sign up to set email alerts
|

Herbal treatment following post‐seizure induction in rat by lithium pilocarpine: Scutellaria lateriflora (Skullcap), Gelsemium sempervirens (Gelsemium) and Datura stramonium (Jimson Weed) may prevent development of spontaneous seizures

Abstract: About 1 week after the induction of status epilepticus in male rats by a single systemic injection of lithium (3 mEq/kg) and pilocarpine (30 g/kg), rats were continuously administered one of three herbal treatments through the water supply for 30 days. A fourth group received colloidal minerals and diluted food grade hydrogen peroxide in tap water, while a fifth group of rats received only tap water (control). Herbal treatments were selected for their historical antiseizure activities and sedative actions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…During the Three Kingdom Period (220–265 A.D.),its use as the first anesthetic for surgery was recorded in literatures [40]. Modern studies showed that D. stramonium had varieties of pharmacological effects including antiasthmatic [41], antiepileptic [42], antioxidant [43], antimicrobial [44], [45], antifungal [46] and anti-inflammatory [47] activities. Approximately 400 complete cp genome sequences have been sequenced in GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…During the Three Kingdom Period (220–265 A.D.),its use as the first anesthetic for surgery was recorded in literatures [40]. Modern studies showed that D. stramonium had varieties of pharmacological effects including antiasthmatic [41], antiepileptic [42], antioxidant [43], antimicrobial [44], [45], antifungal [46] and anti-inflammatory [47] activities. Approximately 400 complete cp genome sequences have been sequenced in GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…There are two studies which show that Gelsemium can have a preventive action against experimental stress (electric shock) in mice 23 or against convulsions provoked by lithium and pilocarpine in rats. 46 It should be noted, that the latter protective effect against convulsions was obtained using a pure extract (24 drops/2 l of drinking water), rather than a homeopathic dilution, mixed with Scutellaria lateriflora (Skullcap) and Datura stramonium (Jimson Weed).…”
Section: Effects In Animal Modelsmentioning
confidence: 99%
“…Used by Zulu as a hypnotic drug against hysteria and as a 'diviner's aid' (Pooley, 2005). Continously treatment with a weak solution of Datura stramonium, Gelsemium sempervirens* and Scutellaria L. (Lamiaceae)* showed possible antiepileptogenic effect in rats (Peredery and Persinger, 2004)…”
Section: Simaroubaceaementioning
confidence: 98%
“…Peredery and Persinger (2004) demonstrated a possible antiepileptogenic effect of a weak solution of Datura stramonium L. (Solanaceae), Gelsemium sempervirens L. (Loganiaceae) Scutellaria lateri flora continuously administrated after lithium pilocarpin induced SE in rats. Interestingly, after removal of extract administration the animals displayed numbers of spontaneous seizures comparable to control group.…”
Section: Crinum Speciesmentioning
confidence: 99%